Educational inequality during isolation for COVID-19 in Buenos Aires - Mariela Cardozo; Corina Aimetta; Sandra Marder (Íconos)
This article presents the results regarding the issue of education from the “Survey on living conditions and infant care during the preventative and obligatory social isolation of COVID-19.” This survey was filled out by a sample of families (n=4,008), whose children were in three levels of public (62.6%) and private (37.4%) education in three districts of the province of Buenos Aires, Argentina. According to the results, the majority of the families sustained communication with the educational institutions; however, cases in which difficulties manifested were linked to limitations in connectivity or lack of technological apparatuses (above all, in public schools). Due to this, the interactions among teachers and students were limited, without the possibility of establishing synchronic communications, which made it difficult to carry out high-quality virtual education over a prolonged period, an impact of the COVID-19 pandemic. Finally, this article concludes by highlighting the limitations and reach of the study in order to analyze issues relating to educational equity and thus contribute to the possibility of designing policies that improve educational access.